Proposal writing guidebook the complete guide to writing winning and successful proposals for funding by funding agencies - Pineda, Danilo D. (Tritium Knowledge Center Pub., 2002)
Purpose: "...tells [you] the step-by-step procedures, techniques, and strategies in writing [your] proposals."